The isolation and functional identification on producing cellulase of Pseudomonas mendocina. Issue 5 (2nd September 2016) - Zhang, Jianfeng; Hou, Hongyan; Chen, Guang; Wang, Shusheng; Zhang, Jiejing
ABSTRACT: The straw can be degraded efficiently into humus by powerful enzymes from microorganisms, resulting in the accelerated circulation of N, P, K and other effective elements in ecological system. We isolated a strain through screening the straw degradation strains from natural humic straw in the low temperature area in northeast of china, which can produce cellulase efficiently. The strain was identified as Pseudomonas mendocina by using morphological, physiological, biochemical test, and molecular biological test, with the functional clarification on producing cellulase for Pseudomonas mendocina for the first time. The enzyme force constant Km and the maximum reaction rate (Vmax) of the strain were 0.3261 g/L and 0.1525 mg/(min.L) through the enzyme activity detection, and the molecular weight of the enzyme produced by the strain were 42.4 kD and 20.4 kD based on SDS-PAGE. The effects of various ecological factors such as temperature, pH and nematodes on the enzyme produced by the strain in the micro ecosystem in plant roots were evaluated. The result showed that the optimum temperature was 28°C, and the best pH was 7.4∼7.8, the impact heavy metal was Pb 2+ and the enzyme activity and biomass of Pseudomonas mendocina increased the movement and predation of nematodes.